2019
DOI: 10.1038/s41598-019-48875-x
|View full text |Cite
|
Sign up to set email alerts
|

Golgin45-Syntaxin5 Interaction Contributes to Structural Integrity of the Golgi Stack

Abstract: The unique stacked morphology of the Golgi apparatus had been a topic of intense investigation among the cell biologists over the years. We had previously shown that the two Golgin tethers (GM130 and Golgin45) could, to a large degree, functionally substitute for GRASP-type Golgi stacking proteins to sustain normal Golgi morphology and function in GRASP65/55-double depleted HeLa cells. However, compared to well-studied GM130, the exact role of Golgin45 in Golgi structure remains poorly understood. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…Based on spectral counts of peptides identified by LC-MS analysis (Supplemental Figure 7C and Supplemental Table 2), G45 was the top hit among 88 proteins identified, an indication that G45 was a physiological binding partner of G55 in our model. G45 is a coiled-coil domain protein that facilitates SNARE-mediated vesicle fusion with Golgi membranes (12,27). High G45 levels were correlated with shorter survival in the TCGA LUAD cohort (Figure 5F), and G45 is a known driver of vesicle biogenesis in the Golgi ( 12), but the mechanism by which G45 drives vesicle biogenesis and the biological significance of G45dependent secretion in cancer remain unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Based on spectral counts of peptides identified by LC-MS analysis (Supplemental Figure 7C and Supplemental Table 2), G45 was the top hit among 88 proteins identified, an indication that G45 was a physiological binding partner of G55 in our model. G45 is a coiled-coil domain protein that facilitates SNARE-mediated vesicle fusion with Golgi membranes (12,27). High G45 levels were correlated with shorter survival in the TCGA LUAD cohort (Figure 5F), and G45 is a known driver of vesicle biogenesis in the Golgi ( 12), but the mechanism by which G45 drives vesicle biogenesis and the biological significance of G45dependent secretion in cancer remain unclear.…”
Section: Resultsmentioning
confidence: 99%
“…In order to investigate the underlying mechanism of impaired acrosome biogenesis in Pfn3 -deficient mice, we performed immunofluorescence (IF) staining by using GM130 and TGN46 antibodies, markers for cis- and trans- Golgi network, respectively. GM130 plays a crucial role in vesicle tethering, fusion, and maintaining cis -Golgi structural integrity ( Tiwari et al, 2019 ), while TGN46 is important for formation of exocytic vesicles and secretion from the trans- part of the Golgi network ( Huang et al, 2019 ). IF revealed cis- and trans- Golgi predominantly concentrated at one pole of the Pfn3 +/+ ( Figures 6A,D ) and Pfn3 +/– ( Figures 6B,E ) spermatids, whereas the Pfn3 –/– spermatids showed defects and disorganization in cis- ( Figure 6C ) and trans -Golgi network ( Figure 6F ).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that Golgin45 and GM130 play a partly redundant role in Golgi structure maintenance 12 . Although these two proteins appear to be unrelated phylogenetically, they share similar arrangement for binding partner interaction, such as GRASPs and Syntaxin5 8 , 10 . As N-terminal domain of GM130 mediates its binding to another vesicle-binding Golgin tether, p115, in a cell cycle-dependent manner via Cdc2 17 , we reasoned that Golgin45-TNKS1 interaction could be also subjected to Cdc2-dependent regulation.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Golgin45 is a Golgi structural protein that has been shown to directly interact with at least four Golgi-associated proteins, including ACBD3, GRASP55, Syntaxin5 and a small GTPase, Rab2-GTP 8 10 . Golgin45 is also called BLZF1, Basic Leucine Zipper Nuclear Factor 1, as it is known to function as a nuclear cofactor 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation